Communication—Wide Bandgap Tin Oxide Thin Film Transistor by Doping Rare Earth Element Europium. (13th July 2020) - Yang, Jianwen; Hu, Gengtao; Cao, Duo; Liu, Feng
Abstract : –Amorphous europium-doped tin oxide ( a- SnEuO) thin film transistors (TFTs) with a wide bandgap of 3.87 eV were prepared by sol-gel method. The results indicate that as Eu content increases, the off-state current of the a- SnEuO TFTs decreases, the threshold voltage (Vth ) shifts in the positive direction and the subthreshold swing ( S.S. ) is also improved. When Eu content is 30 at%, the mobility of a- SnEuO TFTs is 4.5 cm 2 V −1 s −1, with an S.S. of 0.8 V dec −1 . and a switching ratio of 9.5 × 10 6 . Our study indicates Eu-doped SnO2 TFT is expected to be the next generation of display technology.